Oh, dude, that's like basic math, right? So, 2x squared plus x squared is just 3x squared. It's like adding apples to apples, but with math. Easy peasy lemon squeezy!
3x squared - x squared = 2x squared
6x^2, six x squared.
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
3x2 - 2x - 5 = (3x - 5)(x + 1) = 0 gives a solution of x = 5/3 or -1. Was that what you wanted?
Oh, dude, that's like basic math, right? So, 2x squared plus x squared is just 3x squared. It's like adding apples to apples, but with math. Easy peasy lemon squeezy!
3x squared - x squared = 2x squared
2x squared - 3x
x(3x - 2)
Oh, dude, you're hitting me with some math here. So, when you multiply 2x squared by 3x squared, you just multiply the numbers (2 * 3 = 6) and add the exponents (2 + 2 = 4), giving you 6x to the power of 4. It's like algebra on steroids, man.
6x2 + 10x = 2x*(3x + 5)
3x2-2x-8 = (3x+4)(x-2) when factored
2 squared X 3 squared = 5 squared
3x(2x + 1)
(x + 1)(2x - 5)
(x - 1)(3x + 5)
(x - 2)(2x + 7)